Ritual Makan Bersama Keluarga Sebagai Prediktor Kesejahteraan Sosial-Emosional Anak: Sebuah Kajian Literatur - Ai Firli; Taopik Rahman; Risbon Sianturi (Sekolah Tinggi Agama Islam Al-Kifayah Riau, 2026)
The purpose of this study is to characterize the importance of family mealtime customs as a predictor of early childhood social-emotional wellbeing. Eating well-being include social and psychological aspects of shared experiences in addition to nutritional intake. In order to comprehend how regular family dinners promote communication, emotional stability, and a sense of belonging, this study examines a variety of scholarly sources using a qualitative literature review method. According to the findings, children can learn social cues, emotional control, and family values in a regulated setting through ritualized family meals. Additionally, these rituals improve the child's general subjective well-being and act as a buffer against behavioral issues. To sum up, family mealtimes are an essential socio-emotional intervention that promotes children's overall development